The Contextual Qur’anic Interpretation of Jihad - Nur Kumala (AQWAL Journal of Qur'an and Hadis Studies, 2021)
In the 20th century, Indonesia was faced with issues of right-wing extremism in thename of religion which affected the benefit of the people. Several acts of terror, thediscourse of the caliphate, returning to the sunnah, and dictation of takfiri havebecome the center of topics in our country, where the issue of "jihad" against religionand the state is often misinterpreted in a harsh and coercive way. Thus, throughanalyzing the contemporary interpretation of the Double Movement, the interpretationof the verse is more inclined towards more universal values, which are humanist,freedom (al-hurriyah), equality (al-musawwah) and justice (al-'adalah). So that itproduces some understanding that jihad is not just about war, but can be done invarious ways by looking at the contextuality of the times, as in the viewpoint of HabibLutfi, that defending the country and homeland as the term "jihad today" is one of thealternatives in silencing the understanding. “Conventional jihad” brought about byelements in destroying religion and the state, including strengthening knowledge ofhistory, increasing the achievement of the nation's children and understanding ofukhuwah wathaniyah which are interconnected to silence as a form of love for thehomeland and jihad for the advancement of religion and the state.